The Welfare Level of the Households of Minapadi Farmers in Epeesi Village, Basala Sub-District, South Konawe District - Akmal, Hasbi; Limi, Muhammad Aswar; Fyka, Samsul Alam (Department of Agribusiness, Halu Oleo University, 2020)
This research was motivated by the number of farmers who work on minapadi system (paddy-fish integration farming system) in Epeesi Village, Basala Sub-District, South Konawe District in which the welfare level of the minapadi farmers community in the village is not yet known. The purpose of this study was to determine the welfare level of minapadi farmers in the region. The determination of the research area was carried out purposively with the consideration that the village was one of the villages that developed minapadi system in South Konawe District. This research was done in January-February 2020. The number of respondents was 36 households working on minapadi farming system. Data analysis was performed using the indicators from BKKBN and quantitative descriptive analysis technique with cross tables and percentage analysis. The results showed that the average minapadi farmers in Epeesi Village were in KS I with a percentage of 41.67%, so that the welfare level of minapadi farmers in Epeesi Village was still classified low. This is because the community of minapadi farmers has not met all indicators set by BKKBN namely basic needs, psychological needs, development needs, and self-esteem.